HUBUNGAN KEPATUHAN PENGOBATAN HIPERTENSI DAN DUKUNGAN KELUARGA DENGAN RISIKO GAGAL GINJAL KRONIK PADA PASIEN HIPERTENSI DI RSUD KOTA DEPOK - Anasya Firmansyah (2022)
Hypertension is a non-communicable disease (PTM) with an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. The success of hypertension treatment is seen from individual medication adherence. One of the factors of hypertension medication adherence is family support. Compliance with hypertension treatment and family support is very important to prevent complications due to hypertension. One of the complications of hypertension is chronic kidney failure. This study aimed to determine the relationship between hypertension medication adherence and family support with the risk of chronic kidney failure in RSUD Kota Depok. This study is a quantitative study with a cross-sectional approach and was conducted on 86 respondents through purposive sampling method. Data collection uses two questionnaires and one observation sheet. The risk of chronic renal failure in hypertensive patients is at risk level. The risk of chronic kidney failure was not influenced by gender (p=0.784), education (p=0.264), duration of hypertension (p=0.051), hypertension medication adherence (0.760), and family support (p=1,000). However, influenced by age (p=0.003), occupation (p=0.013), and. Hypertension medication adherence and family support were not associated with the risk of chronic kidney failure. Keywords : Hypertension Treatment Compliance, Family Support, Risk Chronic Kidney Failure